Bit-by-Bit Towards Unlimited: An Analysis of Zero Rating and Sponsored Data Practices of Internet Service Providers - Daniel Schnurr; Lukas Wiewiorra (International Telecommunications Society (ITS), 2018)
Zero rating and sponsored data have recently been introduced as new tari↵ options in mobile telecommunications markets. Both practices exempt data traffic of specific Internet services from an Internet user's download limit and thus allow for unlimited consumption of the respective content. Whereas network operators have advertised these options as consumer-friendly innovations, both practices have been criticized by net neutrality proponents and are currently under regulatory scrutiny in several countries. Based on a model of a monopolistic Internet access provider and two advertising-financed content providers, we investigate market outcomes under both zero rating and sponsored data and assess optimal pricing schemes, firms' profits, consumer surplus and total welfare. We then analyze welfare e↵ects if network operators are prohibited from o↵ering service-specific exemptions from users' data allowance and derive policy implications for the current regulatory debate on net neutrality.
Keywords: 330; Internet access; data caps; zero rating; sponsored data; price discrimination; net neutrality; regulation; public policy